Effects of Personality Traits Concerning Media Use Decisions on Fear of Missing Out and Social Media Use Behavior - Sheng-Cheng Lin; Er-Ting Jian (Behavioral Sciences, 2022)
We could view the phenomenon of fear of missing out (FoMO) as a dilemma of too many choices about social media. Although there are already various studies on FoMO, there is still a lack of studies on what personality traits concerning media use decisions will contribute to FoMO or how FoMO mediates these personality traits and people’s social media use behavior, and, thus, corresponding negative emotions. This study explored the causes of FoMO in a FoMO moderated mediation model using maximizing tendency before the choice was made, social comparison orientation when making choices, and regrets tendency after the choice was made. The results showed that (1) there is a non-significant influence between maximizing tendency and FoMO, (2) regret tendency is a positive influence on FoMO, (3) social comparison orientation is a positive influence on FoMO, (4) FoMO is a positive influence on the compulsive use of social media and surveillance use of social media, (5) FoMO exhibited a full mediating effect on the relationship between regret tendency and social media surveillance use, (6) FoMO exhibited a full mediating effect on the relationship between social comparison orientation and social media compulsive use.